Australian Screen Editors. - Australian Screen Editors Guild (Potts Point, NSW : Australian Screen Editors)
"The Australian Screen Editors Guild (ASE) is a cultural, professional and educational organisation, dedicated to the pursuit and recognition of excellence in the arts, sciences and technology of motion picture film and televisual post production. It aims to promote, improve and protect the role of editor as an essential and significant contributor to all screen productions."--About Us.
Title from title screen (viewed on 4 January 2019)
Mode of access: Available Online. Address as at 07/01/2019
Selected for archiving
Keywords: Motion pictures -- Australia; Television -- Australia; Australian